Affordability of Higher Education in South Africa: Are Above Inflation Tuition Fee Increases Justified? - Serfontein, C.; Smit, A. V. A. (International Journal of African Higher Education, 2024)
This article investigates why South African universities increased their tuition fees above inflation during the period 2010 to 2019 (intentionally excluding the potential distortion caused by COVID-19). The affordability of higher education is the subject of increased debate among stakeholders in South Africa. From a financial point of view, universities, as typical service organisations, should have benefited from an increase in enrolments. The main reason is that their expenses are typically period costs and are hence less affected by an increase in enrolments. However, the key findings of the study on which this article is based were that revenue increased above inflation, with tuition fees the main culprit. In turn, the reason for increased tuition fees is a significant increase in expenses. This suggests that universities did not benefit from economies-of-scale or efficiency in managing their expenses. The research makes a unique contribution to the body of knowledge by assessing why university tuition fees increased using a financial model to project budgeted revenue, expenses and tuition fees (taking inflation and growth in student enrolments into account) for 2019 using actual financial data from 2010.